KINERJA KOMISI PEMILIHAN UMUM KABUPATEN SIGI DALAM PENYELENGGARAAN PEMILIHAN UMUM ANGGOTA DEWAN PERWAKILAN RAKYAT, DEWAN PERWAKILAN DAERAH DAN DEWAN PERWAKILAN RAKYAT DAERAH TAHUN 2014 - Potabuga, Faried (Katalogis, 2016)
The aim of this research was to determine the performance Sigi Regency Organizing Elections In the DPR, DPD, and DPRD 2014. In order to measure performance in this study using performance theory put forward by Dwiyanto, include: productivity, quality of service, responsiveness, responsibility, and accountability this research is classified as descriptive, qualitative approach. This study is also the Ex Post Facto research. The study involved a total of 12 (twelve) informant determined purposive. Data is collected using interview techniques and documentation. Analysis of the data in this study include data reduction, data presentation, and Draw conclusions. The results of these studies show performance Election Commission Sigi In the General Election of DPR, DPD and DPRD 2014, if in view of the elements of optimal productivity is already done, the elements are already optimally implemented Responsibility, Accountability elements are already optimally implemented. While the element is not optimal Quality of Service and responsiveness element.